Mechanisms of interaction between the poet and the audience - Meftah AOUADJ (Pensées Genre, Penser Autrement)
This article examines the mechanisms of communication between the poet and the audience, focusing on how poetic imagery conveys sensory experiences. It explores techniques that enhance emotional connections and the harmony between the poet’s objectives and the audience's perceptions. Using analytical and psychological methods, the study highlights the psychological, sound, and semantic aspects that influence the effectiveness of poetry. The findings show that poetic composition impacts emotional engagement, evoking both explicit and implicit meanings, creating a shared experience of pleasure and aesthetic harmony, while emphasizing the need for coherence and depth in poetic elements.